Willingness to pay for human papillomavirus vaccines among Chinese female health care workers - Xin-yue LU; Xiao-ping SHAO; Wei-feng HUANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate the willingness to pay (WTP) for human papillomavirus (HPV) vaccine and its influencing factors among Chinese female health care workers for improving HPV vaccination strategies in China. MethodsAn online survey was conducted among 18 - 45 years old female health care workers from 310 hospitals in 31 provincial level administrative divisions across China during November - December 2021. A self-designed questionnaire was used to collect information on demographics, HPV vaccination status, HPV-related knowledge, protective motivation theory (PMT)-based HPV vaccination-related cognition and attitude, and the amount of WTP for HPV vaccination. Structural equation model was adopted to analyze influencing factors of WTP. ResultsOf the 15 969 valid respondents aged 30.6 ± 6.2 years, 43.4%, 33.2%, and 23.4% reported the highest amount (CNY) of WTP for HPV vaccine ranging 0 - 1 600, 1 601 - 3 200, and 3 201 - 5 000, respectively; higher amount of WTP was reported by the respondents aged 18 - 26 years, being Han ethnic, unmarried/divorced/widowed, having the education of master degree or above, without professional title, with a monthly income more than 8 000 CNY, working in a tertiary hospital, and already receiving HPV vaccination or having an appointment for the vaccination. The scores for multidimensional PMT-based cognition and attitude about HPV vaccination were significantly correlated with HPV vaccine acceptance and the WTP for HPV vaccine (P < 0.001 for all). The structural equation model analysis showed that perceived susceptibility (β = 0.046), perceived severity (β = 0.012), response efficacy (β = 0.027), self-efficacy (β = 0.155), HPV-related knowledge (β = 0.151) and vaccination behavior (β = 0.154) were positively associated with the WTP for HPV vaccination; whereas response cost was negatively associated with the WTP for HPV vaccination (β = - 0.183). ConclusionChinese female health care workers have a relatively higher WTP for HPV vaccination. Price of HPV vaccine, convenience of vaccination/ appointment services, and safety of vaccines remain the main influencing factors of the WTP.